Distinct attitudes of professionals from different medical specialties toward autonomy and legal instruments in the assessment of patients with Alzheimer's disease - Pioltini, Ana Beatriz Maringolo [UNESP]; Mendes-chiloff, Cristiane Lara [UNESP]; Schelp, Arthur Oscar [UNESP]; Marcolino, Everson Da Silva (Associação de Neurologia Cognitiva e do Comportamento, 2010)
The evaluation of competence of Alzheimer's disease (AD) patients to assume personal or collective responsibilities and the resulting legal implications is a relevant issue.

A avaliação da competência de pacientes com doença de Alzheimer (DA) para assumir responsabilidades pessoais ou coletivas e as implicações legais resultantes constituem um tema relevante.
Atitudes distintas de profissionais de diferentes especialidades médicas relacionadas à autonomia e aspectos jurídicos no cuidado de pacientes com demência
Keywords: Alzheimer's disease; attitudes; ethical and legal aspects.; doença de Alzheimer; atitudes; aspectos éticos e legais.